Aspirin in dermatology: Revisited - Aditya Kumar Bubna (Wolters Kluwer Medknow Publications, 2015)
Aspirin has been one of the oldest drugs in the field of medicine, with a wide range of applications. In dermatology, aspirin has shown benefit in a variety of disorders. Recently, reduction of melanoma risk with aspirin has been demonstrated. Although an analgesic to begin with, aspirin has come a long way; after cardiology, it is now found to be useful even in dermatology.